Incidence of early complications in the posterolateral approach to posterior malleolus fractures - Tavares, Camilo Miranda de Pinho; Castilho, Rodrigo Simões; Lopes, Fernando Araújo Silva; Baumfeld, Daniel Soares; Silva, Thiago Alexandre Alves; Pinto, Roberto Zambelli de Almeida (Journal of the Foot & Ankle, 2020)
Introduction: To ascertain the incidence of early complications in the posterolateral approach to open reduction and internal fixation of posterior malleolar fractures and identify possible risk factors related to occurrence of these complications. Methods: Retrospective study carried out in three tertiary hospitals. Patients who underwent open reduction and internal fixation of posterior malleolus fractures via the posterolateral route were divided into two groups: with versus without delayed postoperative healing. To assess risk and protective factors for the outcome of delayed healing, we evaluated the time between trauma and surgery, whether the patient had a fracture-dislocation of the ankle, and whether external fixation was performed before surgery. We also evaluated whether improvement in operative technique led to a reduction in complication rates. Results: A total of 43 individuals who underwent surgical correction of posterior malleolus fractures via the posterolateral route between 2013 and 2018 were included. Of these, 19 (44.2%) had skin complications that led to delayed healing. Skin complications occurred more frequently at the beginning of the learning curve of the surgeons involved; the incidence up to the year 2016 was 56.3%, decreasing significantly to 37% from 2017 onward. Conclusion: Patients who undergo open reduction and internal fixation of posterior malleolus fractures via the posterolateral route at the beginning of the learning curve are a greater risk of developing skin complications, demonstrating the importance of this approach being restricted to more experienced surgeons. Level of Evidence III; Prognostic Studies; Retrospective Study.